2017
DOI: 10.1634/theoncologist.2016-0517
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Response to Nivolumab and Stereotactic Body Radiation Therapy (SBRT) in Neuroendocrine Cervical Carcinoma with High Tumor Mutational Burden: Management Considerations from the Center For Personalized Cancer Therapy at UC San Diego Moores Cancer Center

Abstract: This article reports a patient with a rare metastatic, chemotherapy‐refractory neuroendocrine carcinoma who was treated with stereotactic body radiation therapy (SBRT) combined with anti‐programmed cell death protein 1 antibody. The novel treatment modality of SBRT combined with a checkpoint inhibitor is discussed, as well as the implications of molecular profiling and tumor mutational burden as potential predictors of response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 34 publications
2
75
0
Order By: Relevance
“…Mismatch‐repair status seems to predict response to immune checkpoint blockade, as seen with pembrolizumab in colorectal, gynaecological and biliary tract carcinoma . Immunotherapy (Nivolumab) combined with stereotactic body radiotherapy showed exceptional results in a patient with advanced, chemotherapy‐refractory large‐cell neuroendocrine carcinoma of the cervix with high mutational burden . As a virally mediated tumour, SmCC‐Cx is likely to harbour high antigenicity, which makes it an amenable target for immune modulation, similar to neoplasms with a high mutational burden .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mismatch‐repair status seems to predict response to immune checkpoint blockade, as seen with pembrolizumab in colorectal, gynaecological and biliary tract carcinoma . Immunotherapy (Nivolumab) combined with stereotactic body radiotherapy showed exceptional results in a patient with advanced, chemotherapy‐refractory large‐cell neuroendocrine carcinoma of the cervix with high mutational burden . As a virally mediated tumour, SmCC‐Cx is likely to harbour high antigenicity, which makes it an amenable target for immune modulation, similar to neoplasms with a high mutational burden .…”
Section: Discussionmentioning
confidence: 99%
“…PD‐1 modulates effector T cell activity by binding to one of its ligands, programmed cell death protein 1 ligand 1 (PD‐L1), which is expressed on a wide range of tumour cells. PD‐L1 overexpression has been associated with immune evasion in various tumour types, and provides a rationale for assessing tumour PD‐L1 expression in order to predict benefit from anti‐PD‐1/PD‐L1 immunotherapy, particularly in the setting of mismatch repair deficiency/microsatellite instability . Tumours with high mutational burden have been shown to be amenable to immune modulation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paraghamian et al used nivolumab in a patient with recurrent, metastatic, programmed cell death ligand-1 (PD-L1)-negative small-cell neuroendocrine cervical carcinoma, who experienced a complete response 60. Sharabi et al 61 reported a patient with metastatic, chemotherapy-refractory neuroendocrine carcinoma with bowel obstruction due to a large tumor burden.…”
Section: Recurrent Diseasementioning
confidence: 99%
“…In another patient refractory to chemotherapy, nivolumab combined with stereotactic body radiation therapy (SBRT) and octreotide treatment resulted in near-complete systemic resolution of the disease for at least 101 months [47]. …”
Section: Clinical Experience With Checkpoint Inhibitors In Nensmentioning
confidence: 99%